Ultraviolet B Irradiation Alters the Level and miR Contents of Exosomes Released by Keratinocytes in Diabetic Condition. (4th January 2022) - Wang, Jinju; Pothana, Kartheek; Chen, Shuzhen; Sawant, Harshal; Travers, Jeffrey B.; Bihl, Ji; Chen, Yanfang
Abstract: Ultraviolet B (UVB) stimulates the generation of extracellular vesicles, which elicit systemic effects. Here, we studied whether UVB affects the release and microRNA (miR) content of keratinocyte exosomes (EXs) in diabetic conditions. In vitro, we examined the UVB effects on affecting EX release from keratinocyte HaCaT cells (HaCaT‐EX) pretreated with high glucose. HaCaT‐EX functions were evaluated on Schwann cells (SCs). In vivo, UVB‐induced miR change in skin EXs of diabetic db/db mice was analyzed. The miRs of interest were validated in HaCaT‐EXs. We found that: (1) UVB promoted HaCaT‐EX generation in dose‐ and time‐dependent manners; 100 and 1800 J m −2 of UVB had the most prominent effect and were selected as effective low‐ and high‐fluence UVB in vitro . (2) A total of 13 miRs were differentially expressed >3‐fold in skin EXs in UVB‐treated db/db mice; miR‐126 was the most up‐regulated by low‐fluence UVB. (3) Functional studies revealed that the SC viability was improved by low‐fluence UVB HaCaT‐EXs, while worsened by high‐fluence UVB HaCaT‐EXs. (4) MiR‐126 inhibitor attenuated the effects induced by low‐fluence UVB HaCaT‐EXs. Our data have demonstrated that low‐ and high‐fluence UVBs promote HaCaT‐EX generation but differentially affect exosomal miR levels and functions under diabetic conditions. Abstract : Ultraviolet B irradiation could affect the level, miR‐126 content and functions of exosomes (EXs) released by keratinocytes in diabetic condition. It will advance our understanding of the potential roles of keratinocyte EXs in diabetic complications such as diabetic neuropathy.